Effects of Recovery Time during Magnetic Nanofluid Hyperthermia on the Induction Behavior and Efficiency of Heat Shock Proteins 72. Issue 1 (December 2017) - Jang, Jung-tak; Jeoung, Jin; Park, Joo; Lee, Won; Kim, Yu; Seon, Jiyun; Kim, Minkyu; Lee, Jooyoung; Paek, Sun; Park, Ki; Bae, Seongtae
Abstract In this study, we investigated the effects of recovery time during magnetic nanofluid hyperthermia (MNFH) on the cell death rate and the heat shock proteins 72 (HSP72) induction behavior in retinal ganglion cells (RGCs-5) to provide a possible solution for highly efficient ocular neuroprotection. The recovery time and the heat duration time during MNFH were systematically controlled by changing the duty cycle of alternating current (AC) magnetic field during MNFH. It was clearly observed that the cell death rate and the HSP72 induction rate had a strong dependence on the recovery time and the optimizated recovery time resulted in maximizing the induction efficiency of HSP72. Controlling the recovery time during MNFH affects not only the cell death rate but also HSP72 induction rate. The cell death rate after MNFH was dramatically decreased by increasing the recovery time during MNFH. However, it was also found that the HSP72 induction rate was slightly decreased by increasing the recovery time. These results indicate that applying the appropriate or optimized recovery time during MNFH can improve the induction efficiency of HSP72 by minimizing the cell death caused by cytotoxic effects of heat.